Reactivity to sorbitan sesquioleate affects reactivity to fragrance mix I - Geier, Johannes; Schnuch, Axel; Lessmann, Holger; Uter, Wolfgang (Contact Dermatitis, 2015)
Fragrance mix I (FM I) and its single constituents contain 5% and 1% sorbitan sesquioleate (SSO), respectively. SSO is a rare sensitizer and a potential irritant.To determine whether the outcome of the FM I breakdown test is affected by positive patch test reactivity to SSO.A retrospective analysis of data from the Information Network of Departments of Dermatology, 1998-2013, was performed.The full FM I breakdown test including SSO was tested in 2952 patients. Of these, 154 (5.2%) had a positive patch test reaction to SSO 20% pet. and 2709 (91.8%) had a negative patch test reaction. Positive reactions to one or more of the single fragrances contained in the mix were significantly more common (82.5% versus 57.3%) in SSO-positive patients, who also had more multiple reactions than FM I-positive patients with negative SSO reactions (61.5% versus 21.3% patients with reactions to two or more fragrances).Our results indicate that reactivity to SSO markedly affects the outcome of patch testing with FM I and its single constituents. SSO must be an obligatory part of the full FM I breakdown test, and should ideally be included in the baseline series.
EVALuna2:5525